EFEKTIVITAS PEER ASSESSMENT TERHADAP ACADEMIC BURNOUT DAN SELF EFFICACY PADA MAHASISWA ILMU KEPERAWATAN UIN SYARIF HIDAYATULLAH - Eni Nuraini agustini; Puspita Palupi; Shofiyyah Shofiyyah; Fadillah Rizki Rahmadina (Prodi Ilmu Keperawatan, Fakultas Ilmu Kesehatan, UIN Syarif Hidayatullah Jakarta, 2025)
Abstract Background: High academic demands can exert significant pressure on students, increasing the risk of Academic burnout. Self-efficacy plays an important role in helping students cope with these challenges. Peer assessment has been proposed as a learning strategy to alleviate academic pressure. the aim of this study is to examine the effectiveness of peer assessment in reducing Academic burnout and improving self-efficacy among nursing students at UIN Syarif Hidayatullah. Method: This study employed a quantitative pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 76 nursing students from UIN Syarif Hidayatullah Jakarta. Academic burnout was measured using the Maslach Burnout Inventory–Student Survey (MBI-SS), and self-efficacy was measured using the General Self-Efficacy Scale (GSES). Data were analyzed using the Wilcoxon Signed-Rank Test and N-Gain analysis. Results: The results showed that peer assessment did not significantly reduce academic burnout (p = 0.756, mean N-Gain = −0.020). However, peer assessment significantly increased students’ self-efficacy after the intervention (p < 0.001, Z = −5.382), with a mean N-Gain score of 0.233. Conclusion: The implementation of peer assessment not lead to a meaningful decrease in academic burnout. However, peer assessment significantly improved self-efficacy. This indicates that the peer assessment strategy has the potential to strengthen students’ confidence in facing academic demands, although it has not yet been effective in reducing the level of academic burnout, which is presumed to be influenced by the duration and intensity of its implementation. Keywords : Academic burnout, nursing students, peer assessment, self-efficacy